Pengaruh Work Engagement terhadap Turnover Intention Operator Alat Berat PT MSM Nirwana Putra Kota Bekasi - Pratama, Henky Surya (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
High employee turnover presents significant challenges for organizations, including increased recruitment and training costs, decreased productivity and service quality, weakened financial performance, and a decline in organizational reputation. This study aims to examine the influence of work engagement on turnover intention among heavy equipment operators at PT MSM Nirwana Putra. Employing a quantitative causal research design, the study involved a sample of 66 heavy equipment operators selected through a saturated sampling technique. Data analysis was conducted using simple linear regression, which included tests for data validity and reliability, regression assumptions, and hypothesis testing. The findings revealed a significant negative relationship between work engagement and turnover intention, indicating that higher levels of work engagement are associated with a lower desire among employees to leave the organization. This suggests that fostering employee engagement can be an effective strategy to reduce turnover rates. For future research, it is recommended to broaden the sample by including operators from other companies, and to differentiate between permanent and contract employees. Additionally, incorporating other variables such as job insecurity, workplace conflict, compensation, work incivility, and fatigue may provide a more comprehensive understanding of the factors influencing turnover intention in this sector.